Impactos das fusões e aquisições sobre a concentração industrial: observações preliminares sobre o caso brasileiro, 1996-2000 - Rocha, Frederico (2004)
This paper aims to investigate the role played by M&A transactions in the change of concentration levels in Brazil from 1996 to 2000. Using information from Thomson Financial Securities Data and from the Annual Industrial Survey of IBGE the paper concludes that: (i) the period was marked by a small increase in concentration levels, (ii) different markets had different concentration trajectories. The dispersion levels of concentration changes are very high; (iii) there seems to be a slight participation of M&A in the increase of concentration levels. This participation seems to be greater when eight and twelve firm concentration ratios are considered than when four firm concentration ratio is taking into account, (iv) the increase in concentration does not seem to affect negatively efficiency outcomes.